Investigating the Association Between rs2439302 Polymorphism and Thyroid Cancer: A Systematic Review and Meta-Analysis - Guo, Yawen; Zhang, Wanchen; He, Ru; Zheng, Chuanming; Liu, Xuefeng; Ge, Minghua; Xu, Jiajie (Frontiers in Surgery, 2022)
Background and aims: The extent of surgical treatment for most thyroid cancer (TC) patients remains controversial and varies widely. As an emerging technology, genetic testing facilitates tumor typing and disease progression monitoring, and is expected to influence the choice of surgical approach for TC patients. Recent genome-wide association studies (GWASs) have identified that rs2439302 (8q12) variants near NRG1 are associated with thyroid cancer risk; however, the results remain inconclusive. Therefore, we aimed to perform a meta-analysis to clarify the association between rs2439302 variants and the risk of thyroid cancer. Methods: We search eligible studies using Pubmed, Scopus, Embase, Web of Science, and Cochrane library by July 2021.We analyzed the pooled OR and the corresponding 95% confidence interval (95% CI) of the included studies, and then conducted subgroup analysis according to the ethnicity. We also performed sensitivity analysis to validate the findings. Results: This meta-analysis finally included 7 studies involving 6090 cases and 14461 controls. Results showed that the G allele of the rs2439302 polymorphism was a significant risk factor of thyroid cancer in Allele (G/C), Dominant (GG+GC/CC), Recessive (GG/GC+CC), Homozygote (GG/CC), Heterozygote (GC/CC) models, with pooled ORs of 1.38 (95%CI, 1.31–1.45), 1.51 (95%CI, 1.41–1.62), 1.52 (95%CI, 1.40–1.66), 1.90 (95%CI, 1.71–2.10) and 1.40 (95%CI, 1.30–1.51), respectively. Subgroup analysis showed that rs2439302 polymorphism was associated with higher thyroid cancer risk in different ethnicities with OR > 1.00. The sensitivity analysis exhibited that the results were stable by omitting any included studies. Conclusions: The study revealed that rs2439302 variants were associated with higher thyroid cancer risk, may have a major influence on the choice of operative approach for TC patient.